ANALISIS KEMAMPUAN PEMECAHAN MASALAH DIMENSI TIGA PADA SISWA SMA - Mu’jizatin Fadiana; Puji Rahayu; Muhammad Mukhlasin (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2020)
This study aims to describe the problem solving skills of class X MA Ma'arif 4 Dadapan in solving three dimensional problems. This type of research is quantitative descriptive. Data was collected through tests and interviews with descriptive statistical data analysis techniques that were developed based on indicators of Polya's problem solving abilities. The results showed that students with high ability and were able to use Polya's problem solving steps well, but students with low ability were less able to use it.